Impact of Optimal Unified Power Flow Controller in Electrical Transmission Systems in Reducing Transmission Cost. Issue 16 (2nd October 2017) - Hosseini-Biyouki, Mohammad Mahdi; Jashfar, Sajad; Vahidi, Behrooz; Askarian-Abyaneh, Hossein
Abstract: This paper presents an approach to optimal placement of optimal unified power flow controller (OUPFC) in electrical transmission systems utilizing genetic algorithm (GA), while reducing transmission systems cost using MATLAB and MATPOWER. The proposed approach is based on optimal power flow (OPF) considering optimization of power systems operation conditions. In order to determine the appropriate place for installation of OUPFC, while considering power injection model of this controller, OPF is utilized to obtain multi-objective function of the optimization problem. In this regard, the objective function comprises generation cost, transmission cost, and OUPFC installation cost. The proposed approach is applied to IEEE 30-bus test system, where the obtained results demonstrate remarkable reduction in overall cost of power system.